Job Satisfaction Level of Agricultural Extension Workers in Kirkuk Governorate and Its Relationship with Their Performance Level and Selected Personal Characteristics - Mahmood, Ekhlas Thaer; Mohammed, Khattab Abdullah (American Journal of Biodiversity, 2026)
The present study was conducted to examine the effect of demographic and social factors on the job performance and job satisfaction of agricultural extension personnel, filling the research gap created by the scarcity of field-based research conducted in the Directorate of Agricultural Extension, Kirkuk. The research community consists of (61) extension workers at the Agricultural Extension Training Center, Kirkuk Governorate. A descriptive-analytical approach was applied to fulfill the research objectives. A set of questions was designed to collect the required data, divided into two sections. The first section was designed to collect information about the socio-demographic and professional factors of the research community, such as the level of satisfaction with the supervisor-subordinate relationship, financial satisfaction, work environment satisfaction, and satisfaction with training programs. The second section was designed to measure the level of job performance. A Job Satisfaction Scale, with four dimensions, and a Job Performance Scale were designed to measure the level of job satisfaction and job performance, respectively. Data analysis was conducted using the Statistical Package for Social Sciences (SPSS). The results showed that the level of job satisfaction for extension workers was moderate, as was the level of the four dimensions of job satisfaction. In contrast, the level of job performance was moderate to high. A strong positive correlation was established between job satisfaction and job performance. The majority of the population sampled, at (57.37%), fell within the range of between (25 – 38) years of age. Gender was found to have a limited influence on job performance in favor of males, although this was only found to be statistically significant at a marginal level of )0.34*). Conversely, gender was found to have no influence on job satisfaction. Educational qualification, academic specialization, and years of experience were found to have no influence on job performance and job satisfaction. However, a trend was noted in which the level of job satisfaction declined with an increase in years of experience. Additionally, a strong positive correlation was established between job satisfaction and job performance. Furthermore, Rural upbringing exhibited a statistically significant positive association with job performance (r = 0.293**) without influencing job satisfaction. Additionally, no influence was found for training courses on either job satisfaction and job performance. The findings of this study establish that the major factors affecting job performance and job satisfaction of extension staff in the field relate to actual field experience, professional competence, and nature of extension work.